2017
DOI: 10.1186/s12987-017-0053-6
|View full text |Cite
|
Sign up to set email alerts
|

Is posture-related craniospinal compliance shift caused by jugular vein collapse? A theoretical analysis

Abstract: BackgroundPostural changes are related to changes in cerebrospinal fluid (CSF) dynamics. While sitting up leads to a decrease in cranial CSF pressure, it also causes shifts in the craniospinal CSF volume and compliance distribution. We hypothesized that jugular vein collapse in upright posture is a major contributor to these shifts in CSF volume and compliance.MethodsTo test this hypothesis, we implemented a mathematical lumped-parameter model of the CSF system and the relevant parts of the cardiovascular syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
48
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 27 publications
4
48
2
Order By: Relevance
“…It is also worth mentioning that SIH patients with EVD showed significantly larger decreases in IJVF ratio compared with those without EVD. This phenomenon closely resembles the posture‐related changes of intracranial hemodynamics . As reported in an MRI intracranial physiological study, a collapsed IJV and diversion of venous drainage into the epidural, vertebral, and other deep cerebral or cervical veins were observed in the upright position, while venous outflow presented predominantly through the IJV while supine .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It is also worth mentioning that SIH patients with EVD showed significantly larger decreases in IJVF ratio compared with those without EVD. This phenomenon closely resembles the posture‐related changes of intracranial hemodynamics . As reported in an MRI intracranial physiological study, a collapsed IJV and diversion of venous drainage into the epidural, vertebral, and other deep cerebral or cervical veins were observed in the upright position, while venous outflow presented predominantly through the IJV while supine .…”
Section: Discussionsupporting
confidence: 73%
“…This phenomenon closely resembles the posture-related changes of intracranial hemodynamics. 37 As reported in an MRI intracranial physiological study, a collapsed IJV and diversion of venous drainage into the epidural, vertebral, and other deep cerebral or cervical veins were observed in the upright position, while venous outflow presented predominantly through the IJV while supine. 38 Hence, the lower IJVF ratio is likely an important sign of intense compensation for intracranial hypotension in SIH patients with EVD, who had higher IE than the normal subjects and SIH group without EVD.…”
Section: Discussionmentioning
confidence: 74%
“…In general, spinal compliance is the dominant contributor to the craniospinal compliance because the dura is less confined by the vertebra in the lower region of the spine (lumbar region) compared with the cranium and upper cervical regions. This finding, however, is not consistent with several other studies stating that the cranial vault is the dominant source of craniospinal compliance (almost two‐thirds) …”
Section: Discussioncontrasting
confidence: 99%
“…This finding, however, is not consistent with several other studies stating that the cranial vault is the dominant source of craniospinal compliance (almost two-thirds). 2,28,29 The significant correlations of cranial and spinal compliance contribution with MR-ICP and LPOP respectively support our hypothesis that the craniospinal compliance distribution plays a major role in modulating the ICP. A cranium with higher compliance reserve can accommodate a larger capacity of fluid inside it without an appreciable increase in ICP.…”
Section: Discussionsupporting
confidence: 74%
“…Furthermore, a recent theoretical analysis of CSF compliance has also indicated that IJV collapse likely plays an important role in the CSF dynamics in the upright human [11]. However, neither of these studies investigated how the suggested neck-level pressure reference point is formed and upheld by the well-known jugular venous collapse.…”
Section: Introductionmentioning
confidence: 99%